The Relationship of Adult Education Faculty to Their Schools of Education - Michael Day; Donna Whitson; Donna Amstutz (Adult Education Research Conference, 1998)
This paper reports the findings of a descriptive study examining the relationship of adult education faculty to their schools of education. Comparing responses among adult education faculty, deans of their schools, and a comparable number of deans without adult education faculty, it was found that generally deans considered the lifelong learning theme more meaningful and relevant to their schools than did adult education faculty and that minimal collaboration exists between adult education faculty and their school of education colleagues especially in the preparation of beginning K-12 teachers. Factors that may enhance the worth of adult education in academic settings are also addressed.